(untitled) (Research, Society and Development, 2021)
The present study was carried out between September and October 2020, in Santana do Livramento, Rio Grande do Sul. The experiment aimed to evaluate the reproductive activity of dairy sheep outside the conventional breeding season. Seventeen multiparous Lacaune ewes were used. The hormonal protocol used consisted of the intravaginal implant for a period of seven days of the progesterone hormone, added to the intramuscular injection of equine chorionic Gonadotropin (eCG) at the time of implant removal, at a dose of 400 IU. After treatment the animals were subjected to a period of mating for 5 days. The estrus was recorded with the help of sheep marked with ink on the chest. The sheep presented 52.9% (9/17) of estrus expression rate. The results obtained demonstrate that the hormonal treatment in dairy sheep allows the manifestation of estrus in periods of the year when it would not naturally occur.